Pengembangan Buku Algoritma Euclid Untuk Perhitungan FPB dan KPK - Astuti Astuti; Paskha Marini Thana; Sri Hanipah; Mulyono Mulyono; St Budi Waluya (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2025)
The fundamental mathematical concepts acquired at the elementary level include the calculation of the greatest common divisor (GCD) and the least common multiple (LCM). It is undeniable that students encounter challenges when attempting to solve and determine the value of GCD and LCM. A prevalent pedagogical practice observed in the classroom is the exclusive reliance on methods derived from textbooks. Accordingly, this research is designed to provide educators with additional resources for implementing alternative methods in teaching the material related to GCD and LCM, with a particular focus on facilitating calculations involving large numbers. This study used the research and development method. The data used were the results of expert judgment from mathematics experts. The product produced from this research is the Euclid algorithm book on the calculation of GCD and LCM, for elementary school teachers. This book received a good response from the experts with an average assessment value of 4.43 or classified as very good so it is suitable for use as a reference for teachers.